2015
DOI: 10.1017/s1047951114002698
|View full text |Cite
|
Sign up to set email alerts
|

The effect of milrinone on right and left ventricular function when used as a rescue therapy for term infants with pulmonary hypertension

Abstract: The use of milrinone as an adjunct to nitric oxide is worth further exploration, with preliminary evidence suggesting an improvement in both oxygenation and myocardial performance in this group of infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 36 publications
1
38
0
1
Order By: Relevance
“…Treatment of persistent pulmonary hypertension of newborn (PPHN) with milrinone requires further investigation although there are some case series papers that have found some benefits (fall in oxygenation index, decrease in the inhaled nitric oxide dose, an increase in blood pressure or an increase in indicators of myocardial performance) after milrinone infusion in newborn (term and preterm) infants with pulmonary hypertension [70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of persistent pulmonary hypertension of newborn (PPHN) with milrinone requires further investigation although there are some case series papers that have found some benefits (fall in oxygenation index, decrease in the inhaled nitric oxide dose, an increase in blood pressure or an increase in indicators of myocardial performance) after milrinone infusion in newborn (term and preterm) infants with pulmonary hypertension [70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…However, some animal studies have shown that high doses of dopamine will elevate both systemic and pulmonary vascular resistances, particularly if pulmonary vascular remodeling is present [34]. Milrinone, which inhibits phosphodiesterase (PDE) 3 (cAMP PDE) activity in cardiomyocytes and pulmonary arterial smooth muscle, is viewed as an ‘inodilator' that may be especially useful in the context of left ventricular dysfunction and pulmonary venous hypertension [35]. Since iNO inhibits PDE3 activity both in vitro and in vivo, milrinone may also be particularly effective as adjunctive therapy for iNO [36,37].…”
Section: Cardiac Supportmentioning
confidence: 99%
“…Neonatologist performed TNE may play a pivotal role in the overall management of the neonate with suspected aPH through the timely and accurate diagnosis of PH, exclusion of PH mimics such as cyanotic congenital heart disease and objective evaluation of RV and LV function . Peterson et al reported the use of echocardiographic predictors of survival and necessity of ECMO, high‐frequency oscillatory ventilation (HFOV) and iNO in 63 neonates with pulmonary hypertension . They postulated that the early identification of at‐risk infants, using echocardiography markers, may prompt earlier or more aggressive intervention enabling enhanced patient outcome.…”
Section: Discussionmentioning
confidence: 99%